1996
DOI: 10.1007/bf02446935
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dimebon on coronary blood flow and myocardial contractility

Abstract: The antihistamine Dimebon, which is an Hi-receptor blocker, is shown to act as a moderate coronary vasodilator without exerting a marked effect on myocardial contractility. Key Words: Dimebon; coronary blood flow; myocardial contractilityA major problem in cardiology is sudden cardiac death, which is often preceded by ventricular arrhythmias due to inadequate coronary circulation [7]. Recently, we reported evidence that the Russianmade antihistamine Dimebon (Hi-receptor blocker) exhibits, in various animal mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Based on the results of these studies, Dimebon was classified as a low toxic substance. A pronounced antiarrhythmic effect of Dimebon and its beneficial effect in certain heart conditions have also been emphasized 21–23…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results of these studies, Dimebon was classified as a low toxic substance. A pronounced antiarrhythmic effect of Dimebon and its beneficial effect in certain heart conditions have also been emphasized 21–23…”
Section: Discussionmentioning
confidence: 99%
“…A pronounced antiarrhythmic effect of Dimebon and its beneficial effect in certain heart conditions have also been emphasized. [21][22][23] In summary, Dimebon has a combination of pharmacological and safety properties that suggest the drug as a candidate for the use in the therapy of Alzheimer's disease. The results of the study reported here show that Dimebon has a great potential as a new medication that may not only improve cognitive functions, but, most importantly, may prevent the progression of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, its use as an antihistamine declined with the discovery of more selective drugs. 6 , 23 Studies also have reported antiarrhythmic properties and an effect on coronary blood flow and myocardial contractibility, 24 , 25 even though the possible underlying mechanisms have not yet been determined. More recently, interest in latrepirdine rebounded following a growing interest in the role of histamine receptors (5-hydroxytryptamine 6 (5-HT6) and 5-HT7) in learning and cognitive functions 26 , 27 and studies reporting cognitive-enhancing and neuroprotective functions of latrepirdine.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…Dimebon (Latrepiridine; 2,3,4,5-tetrahydro-2,8-dimethyl-5-(2-(6-methyl-3-pyridyl)ethyl)-1 H -pyrido(4,3-b)indole)) was introduced as an antihistamine in Russia in 1983 (Mateeva 1983) and was subsequently investigated as a possible therapeutic for a variety of disorders (Shadurskii et al 1983; Galenko-Iaroshevskii et al 1995, 1996). Based on its neuroprotective and cognitive-enhancing properties in the CNS (Shadurskaia et al 1986; Lermontova et al 2000; Bachurin et al 2001; Lermontova et al 2001), Dimebon was investigated as a possible treatment for Alzheimer's disease (Doody et al 2008).…”
Section: Introductionmentioning
confidence: 99%